English english - Shakti, Tendri Sanna; Ruslin; Fatima; Alhawsawi, Sajjadllah; Ihsan, Muhammad (LP2M IAIN Sultan Amai Gorontalo, 2025)
Background: In Japanese higher education, the integration of English through English-Medium Instruction (EMI) poses both opportunities and challenges for international students, particularly those from non-English-speaking backgrounds. Aims: This study explores the experiences of Indonesian students in using English for academic purposes in Japanese universities, focusing on their views, challenges, and adaptation strategies. Methods: Using a qualitative case study approach, data were collected through in-depth interviews with five Indonesian postgraduate students studying across diverse academic backgrounds in various universities in Japan. Document analysis was also conducted to support the interview data. Results: This study revealed that English is essential for accessing academic resources and engaging in international interactions. However, students still face challenges in pronunciation, academic writing, vocabulary, presentation norms, and expressing ideas confidently and clearly. They use various strategies such as self-directed learning, digital tools, peer interaction, and institutional support to adapt. Implications: The study highlights the need for more inclusive EMI policies and better language support services in Japanese universities. It also emphasises that language learning in EMI contexts is socially, culturally, and emotionally complex, requiring internal motivation, social interaction, and institutional responsiveness.